Analysis of Water and Sea Rescue Knowledge of ARFF Personnel in Emergency Preparedness Efforts at Juanda International Airport - Michael mayalid; Endang Sugih Arti; Nawang Kalbuana (Jurnal Teknologi Kedirgantaraan, 2026)
Juanda International Airport operates within a 5-mile (±8 km) radius from its reference point, which includes surrounding water areas. As part of its operational responsibility, the airport must ensure the safety and security of passengers, particularly in emergency situations occurring in or near water. The Airport Rescue and Fire Fighting (ARFF) unit is tasked with conducting rescue operations during such emergencies, making it essential for its personnel to possess proper qualifications, knowledge, and practical skills in water and sea rescue procedures.This study aims to assess the level of understanding among ARFF personnel regarding water and sea rescue and to identify the efforts that have been made by the ARFF unit in responding to water-based emergencies around the airport. The research was conducted using observation, interviews, and literature review. Findings indicate that the overall knowledge and preparedness of ARFF personnel regarding water rescue operations remain relatively low.By using the Gap Analysis method, the study found a noticeable difference between the current capabilities of personnel and the standards expected by relevant aviation safety regulations. Therefore, it is recommended that the ARFF unit design and implement structured, ongoing training, incorporating both theoretical and practical sessions, to enhance personnel competence and readiness for water-related emergencies.